(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Bariatric surgery has emerged as a highly effective option for people with obesity, offering significant and sustainable weight loss results. This surgical approach involves several procedures that alter the anatomy of the gastrointestinal tract, leading to a reduction in food intake and nutrient absorption. Established procedures such as sleeve gastrectomy, gastric bypass, adjustable gastric banding, and biliopancreatic diversion with duodenal switch have a proven track record. In contrast, emerging options such as intragastric balloons, AspireAssist devices, and endoscopic sleeve gastroplasty show promise but require further research. Numerous studies have highlighted the remarkable benefits of bariatric surgery, not only in weight loss, but also in resolving obesity-related comorbidities and significantly improving quality of life. However, successful outcomes depend on a multidisciplinary approach, encompassing preoperative assessment, patient selection, comprehensive postoperative care, nutritional support, and psychological counselling. Regular follow-up and adherence to postoperative recommendations are crucial to maintaining weight loss and achieving positive long-term outcomes.